Inference on human history through DNA - Barbujani, Guido (Henry Stewart Talks, 2009)
Human population structure, Racial catalogs based on morphology, Genetic variation within and between populations, Genetic clustering of human populations, Isolation by distance, A recent demographic expansion from Africa, Testing evolutionary hypotheses by coalescent simulation, Ancient DNA